The Effect of Plyometric Training Program on Increasing Vertical Jump Ability in Volleyball Players - Ahmad Muchlisin Natas Pasaribu (Journal Coaching Education Sports, 2026)
Purpose – This study aims to examine in depth the effect of plyometric training programs on improving vertical jumping ability in volleyball players. Design/methodology/approach – The research approach used in this study is a quantitative approach This type of research is a quasi-experimental, This research method involves a pre-test and post-test design with a control group. The population in this study is all high school level volleyball athletes in Bekasi city. Sample of 30 students. The data collection techniques used include vertical jump ability The data analysis techniques used are descriptive and inferential statistical analysis. Findings – This study proves that a plyometric training program significantly improves vertical jumping ability in high school level volleyball athletes in Bekasi city. The experimental group who underwent plyometric training showed a significantly greater increase in vertical jump height compared to the control group who underwent conventional training. These findings support the theories of muscle adaptation and the stretch-approach cycle, and are consistent with previous research showing the effectiveness of plyometric training in improving athletic performance. Limitasi/Novelty- Although this study has limitations, such as the small sample size and short duration of the intervention, the results provide strong empirical evidence that plyometric exercises can be an important component in volleyball training programs to optimize vertical jump performance.